Stability of thin uniperiodic cylindrical shells - Tomczyk, B. (Katedra Wytrzymałości Materiałów i Konstrukcji, Politechnika Łódzka, 2003)
The aim of this contribution is to propose a new averaged model for stability analysis of thin linear-elastic cylindrical shells having the periodic structure along one direction tangent to the shell midsurface. In contrast with the known homogenized models the proposed one makes it possible to describe the effect of the periodicity cell size on the overall shell behavior ( a length-scale effect ). In order to derive the goveming equations with constant or slowly varying coefficients the known tolerance averaging procedurc is applied. The comparison between the proposed model and the model without the length-scale effect is presented.
Keywords: stabilność; uśrednianie tolerancyjne; cienkie jednokierunkowe cylindryczne muszle; stability; tolerance averaging; thin unidirectional cylindrical shells